Postoperative Nausea and Vomiting in Female Patients Undergoing Breast and Gynecological Surgery: A Narrative Review of Risk Factors and Prophylaxis - Echeverria-Villalobos, Marco; Fiorda-Diaz, Juan; Uribe, Alberto; Bergese, Sergio D. (Frontiers in Medicine, 2022)
Postoperative nausea and vomiting (PONV) have been widely studied as a multifactorial entity, being of female gender the strongest risk factor. Reported PONV incidence in female surgical populations is extremely variable among randomized clinical trials. In this narrative review, we intend to summarize the incidence, independent predictors, pharmacological and non-pharmacological interventions for PONV reported in recently published clinical trials carried out in female patients undergoing breast and gynecologic surgery, as well as the implications of the anesthetic agents on the incidence of PONV. A literature search of manuscripts describing PONV management in female surgical populations (breast surgery and gynecologic surgery) was carried out in PubMed, MEDLINE, and Embase databases. Postoperative nausea and vomiting incidence were highly variable in patients receiving placebo or no prophylaxis among RCTs whereas consistent results were observed in patients receiving 1 or 2 prophylactic interventions for PONV. Despite efforts made, a considerable number of female patients still experienced significant PONV. It is critical for the anesthesia provider to be aware that the coexistence of independent risk factors such as the level of sex hormones (pre- and postmenopausal), preoperative anxiety or depression, pharmacogenomic pleomorphisms, and ethnicity further enhances the probability of experiencing PONV in female patients. Future RCTs should closely assess the overall risk of PONV in female patients considering patient- and surgery-related factors, and the level of compliance with current guidelines for prevention and management of PONV.